2000
DOI: 10.1073/pnas.97.20.10960
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment for murine keratinocyte stem cells based on cell surface phenotype

Abstract: The identification and physical isolation of epithelial stem cells is critical to our understanding of their growth regulation during homeostasis, wound healing, and carcinogenesis. These stem cells remain poorly characterized because of the absence of specific molecular markers that permit us to distinguish them from their progeny, the transit amplifying (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
299
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(317 citation statements)
references
References 31 publications
12
299
0
6
Order By: Relevance
“…2I-L). It has been noted that stem cells isolated from other tissues such as the skin and hair follicle [43][44][45] have smaller cell sizes than their more differentiated progeny. The SP cell frequency in rat corneal epithelium (4.6%) was also much higher than in the limbus, as well as results reported for several tissues and organs [13,16,20,23], and the presence of corneal epithelial SP cells in rat eyes were contrary to our previous results for both human [23] and rabbit [24].…”
Section: Discussionmentioning
confidence: 99%
“…2I-L). It has been noted that stem cells isolated from other tissues such as the skin and hair follicle [43][44][45] have smaller cell sizes than their more differentiated progeny. The SP cell frequency in rat corneal epithelium (4.6%) was also much higher than in the limbus, as well as results reported for several tissues and organs [13,16,20,23], and the presence of corneal epithelial SP cells in rat eyes were contrary to our previous results for both human [23] and rabbit [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface receptor molecules are particularly useful for isolating and maintaining specific cell subsets in vitro for investigational studies (Kaur and Li, 2000). However, reliance on cell adhesion molecules alone is inadequate for the purification of stem cell candidates, because almost all basal keratinocytes express, to varying degrees, these molecules which are essential for many different biological processes (Peltonen et al, 1989;Carter et al, 1990;Dowling et al, 1996;Hodivala-Dilke et al, 1998;Tani et al, 2000). Kaur and colleagues have identified and enriched putative stem cells from epidermal keratinocytes (Peltonen et al, 1989;Li et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…2 FACS analyses revealed that B18% of total epidermal cells were integrin b1 + (b1 + ) and 6.5% were CD71 + compared with the isotype control. The 14.1% of primary keratinocytes that were b1 + CD71 À cells were efficiently enriched by FACS to 91.2% purity (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Candidate murine keratinocyte stem cells express high levels of b1 integrin and low levels of the transferrin receptor, CD71 (b1 integrin + CD71 À ). 2 Additional markers of hair follicle stem cells include the combination of high expression of integrin a6 (a6+), low levels of CD71 (CD71 À ) and high CD34 levels. 2 Hair growth, differentiation and regeneration involve several signaling pathways, 3 including Wnt signaling, an important pathway in hair growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation